2004
DOI: 10.1038/sj.bjc.6601718
|View full text |Cite
|
Sign up to set email alerts
|

The tumour–stromal interaction between intratumoral c-Met and stromal hepatocyte growth factor associated with tumour growth and prognosis in non-small-cell lung cancer patients

Abstract: Immunohistochemical analyses of the effects of hepatocyte growth factor (HGF) and c-Met expression on tumour growth and angiogenesis were performed on 88 patients with non-small-cell lung cancers (NSCLCs). In all, 22 carcinomas (25.0%) were intratumoral HGF-positive, 14 carcinomas (15.9%) were stromal HGF-positive, and 36 carcinomas (40.9%) were intratumoral c-Metpositive. None of the carcinomas were stromal c-Met-positive. Examination of tumour growth revealed that the frequency of tumours with a high Ki-67 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
110
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(116 citation statements)
references
References 33 publications
3
110
3
Order By: Relevance
“…Here, we also show that high expression of pCMET is related to poor prognosis and high expression of E-cadherin is related to improved outcome (Bremnes et al, 2002;Masuya et al, 2004b). We found KRAS mutations to be related to favourable prognosis, which contrasts the existing literature that indicates these mutations to be a negative prognostic factor (Van Zandwijk et al, 1995;Miyake et al, 1999).…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Here, we also show that high expression of pCMET is related to poor prognosis and high expression of E-cadherin is related to improved outcome (Bremnes et al, 2002;Masuya et al, 2004b). We found KRAS mutations to be related to favourable prognosis, which contrasts the existing literature that indicates these mutations to be a negative prognostic factor (Van Zandwijk et al, 1995;Miyake et al, 1999).…”
Section: Discussioncontrasting
confidence: 54%
“…Several other markers have also been associated with poor prognosis in NSCLC (EGFR, CMET, E-cadherin, pAKT (Takanami et al, 1996;Bremnes et al, 2002;David et al, 2004;Deeb et al, 2004;Masuya et al, 2004a)), but at present there is no single marker that can be used to guide therapy or predict prognosis of NSCLC patients.…”
mentioning
confidence: 99%
“…In striking contrast to our results, expression of MET/HGF in solid malignancies has been associated with unfavorable clinical outcomes, 16,17,19,20,22,25 although a few studies identified a favorable prognostic impact of MET. 36,37 Expression of MST1R is also associated with unfavorable clinical outcomes [38][39][40] or not associated with prognosis.…”
Section: Discussioncontrasting
confidence: 99%
“…24 Previous studies also report that MET/HGF has prognostic significance in many malignant tumors. 19,20,25 MST1R (RON), an RTK with homology to MET, is involved in tumor progression and metastasis. 26,27 MST1R is overexpressed in human epithelial malignancies.…”
mentioning
confidence: 99%
“…4 Modern literature accordingly emphasizes the search for new biological prognostic markers in order to refine the prognostic value contributed by tumor staging and histopathological analyses. [4][5][6][7][8][9] Among the biological markers whose diagnostic and prognostic values have already been demonstrated in various types of cancers are galectins in general, [10][11][12] and galectin-3 in particular. 13,14 In all, 14 galectins have been identified to date 10,11 which function as cell receptors for the N-acetyl-lactosamine (LacNAC) moieties present on most of the extracellular matrix components.…”
mentioning
confidence: 99%